Mixed methods applications in action research : from methods to community action - Ivankova, Nataliya V. (Los Angeles, CA : SAGE Publications, Inc., 2015)
This first-of-its-kind book provides readers with the information they need to design and conduct a mixed methods action research (MMAR) study in a practical and pragmatic manner. Using a multidisciplinary focus, the author provides a scholarly and applied orientation to meet the varied epistemological and professional needs of scholar practitioners. The book is applicable to broad audiences with different levels of research skills, including students learning how to conduct research in practical settings, practitioners faced with the need to address pertinent issues in their professional practices, community leaders seeking to inform policy changes, and college faculty who teach research methods and conduct funded research in collaboration with practitioner-researchers and community stakeholders. A wide variety of pedagogical features make it appropriate for use as an instructional text aimed at developing skills in designing, conducting, implementing, and reporting an action research study that integrates mixed methods.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Action research; Education -- Research -- Methodology